2003
DOI: 10.1076/clin.17.3.395.18087
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Pain Report in Litigants With Malingered Neurocognitive Dysfunction

Abstract: Twenty-nine litigants who met criteria for either definite or probable malingered neurocognitive dysfunction and reported chronic pain produced scores on the McGill Pain Questionnaire (MPQ), Pain Disability Index (PDI), and Modified Somatic Perception Questionnaire (MSPQ) that were significantly higher than scores produced by large samples of clinical pain patients. At 0.90 specificity, the MPQ, PDI, and MSPQ yielded sensitivities of 0.21, 0.59, and 0.90, respectively. The MSPQ alone, correlated significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 31 publications
5
42
1
Order By: Relevance
“…It was further hypothesized that patients who failed the TOMM would perform more poorly on tests of cognitive ability than would those patients who passed the TOMM. Overall, the results supported these hypotheses and are consistent with literature focusing on the association of poor effort and lower performance on objective neurocognitive tests following TBI (e.g., Gervais et al, 2004;Green, 2007;Locke et al, 2008), exaggerated self-reported postconcussion symptoms following MTBI Tsanadis et al, 2008), and exaggerated selfreported symptoms (not post-concussion-specific) in both non-TBI and TBI samples (Boone & Lu, 1999;Gervais et al, 2008;Gervais et al, 2004;Larrabee, 2003bLarrabee, , 2003cLocke et al, 2008;Ruocco et al, 2008;Stevens et al, 2008;Suhr et al, 2008;Suhr et al, 1997;Wygant et al, 2007). In this study, compared to MTBI patients who passed the TOMM, MTBI patients who failed the TOMM (a) endorsed more postconcussion symptoms on the PCS, (b) endorsed more cognitive complaints on the BC-CCI, and (c) had lower scores on the Attention, Memory, and Executive Function indexes of the S-NAB.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was further hypothesized that patients who failed the TOMM would perform more poorly on tests of cognitive ability than would those patients who passed the TOMM. Overall, the results supported these hypotheses and are consistent with literature focusing on the association of poor effort and lower performance on objective neurocognitive tests following TBI (e.g., Gervais et al, 2004;Green, 2007;Locke et al, 2008), exaggerated self-reported postconcussion symptoms following MTBI Tsanadis et al, 2008), and exaggerated selfreported symptoms (not post-concussion-specific) in both non-TBI and TBI samples (Boone & Lu, 1999;Gervais et al, 2008;Gervais et al, 2004;Larrabee, 2003bLarrabee, , 2003cLocke et al, 2008;Ruocco et al, 2008;Stevens et al, 2008;Suhr et al, 2008;Suhr et al, 1997;Wygant et al, 2007). In this study, compared to MTBI patients who passed the TOMM, MTBI patients who failed the TOMM (a) endorsed more postconcussion symptoms on the PCS, (b) endorsed more cognitive complaints on the BC-CCI, and (c) had lower scores on the Attention, Memory, and Executive Function indexes of the S-NAB.…”
Section: Discussionsupporting
confidence: 86%
“…COGNITIVE EFFORT AND SELF-REPORTED SYMPTOMS 963 defendants ; (d) exaggerated selfreported attention-deficit/hyperactivity disorder (ADHD) symptoms (Suhr, Hammers, Dobbins-Buckland, Zimak, & Hughes, 2008), and (e) exaggerated self-reported pain symptoms in personal injury litigants (86% alleged MTBI, Larrabee, 2003c, andnon-head-injured disability claimants, Gervais, Rohling, Green, &Ford, 2004). In contrast, some researchers have failed to support a relation between effort tests and self-reported symptoms, with no association found between effort test performance and (a) Millon Clinical Multiaxial Inventory (MCMI-III) scale elevations in personal injury litigants (94% TBI; Ruocco et al, 2008); (b) self-reported symptoms of anxiety, posttraumatic stress disorder (PTSD), depression, nonsyndromal psychiatric complaints, or whiplash, in personal injury litigants (32% TBI; Stevens, Friedel, Mehren, & Merten, 2008); or (c) self-reported depression and anxiety in treatment-seeking patients following acquired brain injury (Locke, Smigielski, Powell, & Stevens, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that we also excluded people if they were identified as providing exaggerated symptom reporting based on the PAI validity scales. The relation between symptom exaggeration and poor cognitive effort is well established [68][69][70][71][72][73][74][75][76][77][78][79]. As such, the combination of the WMT and PAI validity scales together greatly reduces the likelihood of misidentification and is unlikely to have affected the overall results.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Criterion B Evidence from neuropsychological testing Example: performance statistically significantly below chance on forced-choice testing (or) Performance below cutting scores on well-validated tests of cognitive feigning (or) Discrepancy between test data and known patterns of brain functioning (or) Discrepancy between test data and observed behavior (or) Discrepancy between test data and reliable collateral reports (or) Discrepancy between test data and documented background history Criterion C Evidence from self-report Example: self-reported history is discrepant with documented history (or) Self-reported history is discrepant with known patterns of brain functioning (or) Self-reported symptoms are discrepant with behavioral observations (or) Self-reported symptoms are discrepant with data from collateral informants (or) Evidence from self-report inventories of exaggeration or fabrication of psychological dysfunction Criterion D Behaviors meeting criteria B or C are not fully accounted for by psychiatric, neurological, or developmental factors Example: psychosis, mental retardation, etc.… Source: Slick et al (1999) symptom overreporting scale on the Psychological Screening Inventory. Although some attention has been devoted to detecting feigned somatic symptoms on the MMPI-2 (Larrabee 2003(Larrabee , 2007aBianchini et al 2008) and MMPI-2-RF (Wygant et al 2009), much of the work in this broad area by mental health professionals has involved identification of feigned pain symptoms. Drawing on Slick et al (1999), Bianchini et al (2005) proposed a diagnostic framework for identifying malingered pain-related disability, as outlined in Table 3.…”
Section: Detecting Feigned Physical or Somatic Symptomsmentioning
confidence: 99%